Celebrating Christine Watkins' 29th Birthday - Watkins, Howard::::::::: (1978)
Christine Watkins, John Ogelsby, Jeannie Ogelsby, Don Leet, ?, ?, ? ? Buffet on dining table--Pacific Gas and Electric spool top